Assessing embodied interpersonal emotion regulation in somatic symptom disorders: a case study - Okur Güney, Zeynep; Sattel, Heribert; Cardone, Daniela; Merla, Arcangelo (Frontiers in Psychology, 2015)
The aim of the present study was to examine the intra- and interpersonal emotion regulation of patients with somatic symptom disorders (SSD) during interactions with significant others (i.e. romantic partners). We presented two case couples for analysis. The first couple consisted of a patient with SSD and his healthy partner, whereas the second couple consisted of two healthy partners. The couples underwent an interpersonal experiment that involved baseline, anger interaction and relaxation phases. During each phase, partners’ cutaneous facial temperature, heart rate and skin conductance levels were measured simultaneously. Participants’ trait-emotion regulation, state-affect reports for self and other, and attachment styles were also examined. The experimental phases were successful in creating variations in physiological processes and affective experience. As expected, emotion regulation difficulties predicted higher increase in the course of temperature in each phase. Besides, the patient showed restricted awareness and reflection to emotions despite his higher autonomic activity compared to healthy controls. Both partners of the first couple revealed limited ability in understanding the other’s emotions, whereas the second couple performed relatively better in that domain. The temperature variations between the patient and his partner showed significant correlations while the correlations of temperature changes between the second couple were negligible except anger phase. The study supported the merits of an embodied interpersonal approach in clinical studies. The tentative results of the cases were discussed in the light of findings in emotion regulation and attachment research.